Metaanalyzing The Effect of Quantum Teaching Model on The Competence of Understanding Science Learning Concepts - Tanjung, Mardia Roza; Fitri, Nici Jumatul; Ayudia, Riri (Journal of Teaching and Learning Physics, 2024)
Understanding concepts in science learning is something that absolutely must be mastered by students. Various studies have been conducted by researchers to obtain the best model or approach to improve students' understanding of concepts. One of them is the Quantum teaching model. This research is a meta-analysis of 24 articles from national and international journals that have been accredited and have an ISSN. The results of the meta-analysis show that there is an influence of the Quantum Teaching model on the competence of Concept Understanding in science learning. Judging from the level of education, the Quantum Teaching model has the highest influence at the elementary level. Meanwhile, in terms of the materials and teaching media used, the highest influence was obtained on the phet media and followed by the use of LKS or LKPD.